A peculiar indifference: the neglected toll of violence on Black America - Currie, Elliott (Metropolitan Books, Henry Holt and Company, 2020)
"In the United States today, a young black man has a sixteen times greater chance of dying from violence than his white counterpart. Violence takes more years of life from black men than cancer, stroke, and diabetes combined. Even black women are more affected by violence than white men, despite its usual gender patterns. These disparities translate into starkly divergent experiences of life and death for whites and blacks in the United States. Yet aside from occasional flare-ups of violence that periodically hit the headlines, the problem has largely receded into the background of public discussion and has nearly disappeared as a target of public policy. The country has been understandably outraged by the recent spate of police shootings of black Americans. But as acclaimed criminologist Elliott Currie points out, the far more widespread problem of "everyday" violent death and injury in black communities has received much less sustained attention or concern. Yet both kinds of violence reflect the same underlying condition: the continuing marginality and structural disadvantage of many black communities in America today. Our unwillingness to confront those conditions helps to perpetuate a level of preventable trauma and needless suffering that has no counterpart anywhere in the developed world. Compelling and accessible, drawing on a rich array of both classic and contemporary research, A Peculiar Indifference describes the dimensions and consequences of this enduring emergency, explores its causes, and offers an urgent plea for long-overdue social action to end it"--